EMPOWERMENT OF WOMEN THROUGH FAMILY WELFARE PROGRAMS (PKK) BASED ON GENDER EQUALITY IN NAURU WIFE IN PAYUNGA VILLAGE BATUDAA GORONTALO DISTRICT - KARSUM ZAIN; ABD. HAMID ISA; MISRAN RAHMAN (International Journal of Innovations in Engineering Research and Technology, 2021)
The involvement of women which is obvious but clearly not yet recognized in Indonesia has an impact on the role of women in family life. The phenomenon that occurs in society is that the increasing number of women helping their husbands find additional income, apart from being driven by the economic needs of the family, women are also increasingly able to express themselves in the midst of the family and society. The economic condition of the family affects the tendency of women to participate in the labor market, in order to help improve the family economy. The type of research used in this thesis is qualitative research which is more of a case study. Case study research is research that explores a problem with specific boundaries, has in-depth data collection, and includes various sources of information. This research is limited by time and place and the cases studied are programs, events, activities, or individuals.